«А дівчат амазонки привчали до зброї, коней та полювання…» - Фіалко, О.Є. (Археологія і давня історія України, 2020)
У статті розглянуто серію поховань скіфських
дівчаток зі зброєю. Завдяки аналізу поховальних
комплексів доводиться коректність віднесення дітей до групи амазонок. According to ancient authors Amazons treated their
new-borns differently. They usually gave the boys to their
fathers. At the same time, they raised the girls themselves.
Moreover, the girls since childhood were taught martial art
and hunting. That is, first of all they were taught archery
and horseback riding. Based on these data, we drew attention
to the Scythian girls’ graves with weapons.
17 such burials of girls are known today in the area
of European Scythia. They are fixed on the territory of
the Steppe Dnieper Region, Crimea, Transnistria and
Don Region.
All children’s graves are individual except for one
(with a teenager-servant). Only two of them were
robbed in antiquity.
All graves (with one exception) were excavated in the
kurhans. An analysis of the types of burial structures
showed that undercut graves and catacombs predominate.
Simple pits are represented by only two cases.
The spread of these types of graves on different regions
coincides with the same graves of adult Amazons.
All burials were made according to the rite of inhumation.
The western orientation of the dead is predominant.
In general, burial sites, rites and anthropological
types of Amazons are identical to those recorded for
the population of European Scythia.
Material support is divided in three main groups:
1) universal (meat meals with a knife and utensils);
2) Female (spindles with spinners, earrings, necklace,
bracelets, rings, stone dishes); 3) Male (weapons, horse
bridles, hryvnias). The combination of the components
of these kits has usually marked the burial of the Amazons.
The nature of the weapon shows that it was intended
primarily for the remote combat.
The evidence of social stratification is, first of all, the
size of burial structures and the composition of material
support. According to these indicators, three social groups
are distinguished in the Amazon girls’ environment.
The chronological range of the burial complexes of
girls with weapons is determined from the end of the
5th to 3—2 centuries BC. However, the main group of
these tombs is dated 4th century B.C.